Vitreous Hemorrhage in Dr.Sardjito General Hospital - Irene Titin Darajati; Firman Setya Wardhana; Mohammad Bayu Sasongko; Supanji Supanji; Tri Wahyu Widayanti; Angela Nurini Agni (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Vitreous hemorrhage is the extravasation of blood in the vitreous cavity of the eye. It cause mild vision impaired to blindness. Moreover, vitreous hemorrhage obscures the posterior segment and if severe and non-traumatic, may lead to diagnostic dilemmas unless associated with classic systemic sign and symptoms. Objective : To provide data regarding causes and clinical aspects of vitreous hemorrhages to guide clinicians in better delineating the expected etiologic patterns of these hemorrhages. Methods: We collected medical records of patient who diagnosed vitreous hemorrhages in Dr. Sardjito General Hospital Jogjakarta between March 2015-March 2016. Characteristics of patients to be explored: age, visual acuity and gender. The data were analyzed descriptive quantitative.Results: There were 189 patients (200 eyes) who diagnosed vitreous hemorrhage in first examination. Fifty three percent of them were male and 47 % were female, most of them were over 50 years old (67.2%) and 32.8% were under 50 years old. The causes of vitreous hemorrhage were proliferative diabetic retinopathy in 131(69.3%), age-related macular degeneration (AMD) 17(9%), retinal vein occlusion 11(5.8%), retinal tear 8(4.2%), Posterior Vitreous Detachment 4(2.1%), vasculitis 3(1.6 %), Polypoidal Choroid Vasculopathy 2(1.1%), trauma 2(1.1%), Eales disease 1(0.5%), and unknown 10(5.3%) patients. Vitreous hemorrhage caused by diabetic retinopathy had vast range of visual acuity (6/7,5- Light Perception) and the worst was among patients with AMD.Conclusion: Most of vitreous hemorrhages caused by proliferative diabetic retinopathy. AMD give the worst visual acuity. Keywords: Vitreous hemorrhage, etiology, visual acuity